The discursive construction of conflict in participatory forest management: The case of the Agoua forest restoration in Benin - Latifou Idrissou (Conservation & Society, 2011)
The Agoua Forest in Benin was declared a protected area in 1953 and subsequently managed by means of a coercion system, which, however, did not prevent its deforestation. In 2002, a participatory management process was designed to restore this forest. Although the project managers and local communities agreed to a plan at the beginning of the process, the plan was not implemented because conflict arose in the course of the process. In this paper, an interactional framing approach was used to analyse the emergence of this conflict, which ended in an impasse. This study showed that the conflict was constructed and evolved mainly in stakeholders′ discourses, even without changes in actual forest management and use. Moreover, it became clear that stakeholders constructed different frames in different conversation contexts: stakeholders, who share a set of perceptions, norms, and expectations as constructed and expressed in their talks (we-groups), constructed stereotypes and stigmas, blaming the other party and presenting themselves as innocent victims. In conversations involving all stakeholders, people did not reveal their real thoughts, either about each other or about the proposals for conflict resolution. This study shows the relevance and agency of discourse in conflict, and the importance of the interactional framing approach in understanding participatory management, and conflict dynamics. It reveals how by means of discourses, farmers in the Agoua Forest succeeded in handling the conflict, with the effect that little has been done in the project′s decision to implement the plan.